A comparative study of using one-stage pattern recognition system to two stage system for robot localization - Su, Eileen Lee Ming; Tiagrajah Janahiraman; Shamsudin Mohd. Amin; Rosbi Mamat; Horvath, Laszlo; Asian Control Conference (4th : 2002 : Singapore) (Skudai : Universiti Teknologi Malaysia, 2002)
20